Environmental flow assessment: recent examples from Sri Lanka - Dissanayake, Priyanka; Weragala, Neelanga; Smakhtin, Vladimir U. (2010)
Assessment and provision of Environmental Flows (EF) is important for the protection of aquatic ecosystems. EF are a set of discharges of a particular magnitude, frequency and timing that are necessary to ensure a certain range of benefits from a river. Such flows need to be scientifically determined and economically justified. Limited exposure to the concept of EF exists in developing countries. This paper gives two recent relevant example studies, which were conducted by IWMI, with foci on EF Assessment (EFA) and valuation of EF benefits in the Walawe and Menik Ganga river basins located in a semi-arid zone of southern Sri Lanka. The Walawe example illustrates the simple method for estimation of EF. The EF are approximated at two sites along the main stream of the Walawe River, which are located below the two main reservoirs. A desktop method is used, which is based on simulated, unregulated daily flow time series and their flow duration curves. The study also illustrates how the required hydrological information can be generated for the locations where EF assessment is intended ? quickly and in conditions of limited observed data. The second Menik Ganga example is used as a case study to evaluate the costs and benefits of environmental water allocations. The EF components evaluated include the water needs for religious festivals, and the requirements of the Yala National Park, the Pilinnawa coastal wetland and grasslands, and the Yala Fisheries Management Area (YFMA) off the coast. Almost all estimates are based on use values of EF such as marketed goods and recreation. The paper intends to stimulate discussion and further research in the fields of EF assessment and economic valuation.